FACTORS THAT DETERMINE STOCK RETURNS MODERATED BY STOCK TRADING VOLUME IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE 2017-2021 PERIOD - Siti Rahmi Hidayatullah; Elfiswandi Elfiswandi; Zefri Yenni (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
This research is motivated by the movement of the average stock return in manufacturing companies that are fluctuating or unstable. This study aims to determine and analyze the effect of return on assets, current ratio, earnings per share on stock returns with stock trading volume as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This study is a quantitative study with a total population of all manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period with a total of 191 companies. The sampling technique of this research is purposive sampling technique with a total sample of 56 manufacturing companies listed on the IDX. The research data is secondary data in the form of financial reports which are accessed through the official website of the IDX (www.idx.co.id). This study was analyzed through MRA (Moderated Analysis Regression) analysis using Eviews 9. The results of this study found that return on assets, current ratio, and earnings per share partially had a significant effect on stock returns in manufacturing companies listed on the Indonesia Stock Exchange (IDX). period 2017-2021. The results of the Moderated Regression Analysis (MRA) test show that stock trading volume (TVA) moderates the effect of the current ratio on stock returns, but stock trading volume (TVA) cannot moderate the effect of return on assets and earnings per share on stock returns in manufacturing companies. listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021.